Frankness, Greek Culture, and the Roman Empire - Fields, Dana Farah (Routledge Monographs in Classical Studies, 2020)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- Preface -- Abbreviations -- 1. Parrhēsia, frankness, and post-classical politics -- 2. Speaking freely -- 3. Kings: frankness to power -- 4. Dēmos: rhetoric in the post-classical city -- 5. Elites: hierarchy, oligarchy, and friendship -- 6. Authorizing frankness: Lucian's satire -- Conclusion -- Bibliography -- Index.